An invisible enemy: Covid-19 and its impact on mental health (Research, Society and Development, 2021)
COVID-19 brought several challenges to Brazil and the world. In addition to the biological, social and economic impacts, the new coronavirus has greatly compromised people's mental health, whether due to the possibility of exposure to contagion, the impact arising from social distancing or the fear of death. This study is a narrative literature review using bibliographical research, descriptive research and qualitative nature, with the aim of presenting knowledge related to mental health during COVID-19 specifically on the impacts on mental health caused by the virus. We searched for materials in several databases (Google Scholar, SciELO, PubMed, Lilacs, among others), as well as using some descriptors to filter the search by content, such as “Covid-19”, “Sars- Cov-2”, “pandemic”, “social distancing” and “mental health”. In conclusion, the literature indicates that a good part of the population was affected, developing some mental disorder during this period, especially anxiety and depression. It is important to create strategies to promote quality of life and well-being in times that are so favorable for mental illness.